2023
DOI: 10.1007/s00018-022-04684-6
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine botulinum toxin A administration promotes endometrial regeneration mediated by IGFBP3-dependent OPN proteolytic cleavage in thin endometrium

Abstract: Adequate endometrial growth is a critical factor for successful embryo implantation and pregnancy maintenance. We previously reported the efficacy of intrauterine administration of botulinum toxin A (BoTA) in improving the endometrial angiogenesis and the rates of embryo implantation. Here, we further evaluated its potent therapeutic effects on the uterine structural and functional repair and elucidated underlying molecular regulatory mechanisms. This study demonstrated that a murine model of thin endometrium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Further studies found that intrauterine BoTA injection improved the endometrial environment in mice with TE by increasing endometrial tolerance and angiogenesis via the regulatory effect of IGFBP3 on hydrolytic cleavage of OPN proteins; these findings suggest BoTA as a potential therapeutic strategy for patients with TE. However, there is currently insufficient basis for clinical trials, and clinical validation is needed ( 45 ).…”
Section: Te Treatmentsmentioning
confidence: 99%
“…Further studies found that intrauterine BoTA injection improved the endometrial environment in mice with TE by increasing endometrial tolerance and angiogenesis via the regulatory effect of IGFBP3 on hydrolytic cleavage of OPN proteins; these findings suggest BoTA as a potential therapeutic strategy for patients with TE. However, there is currently insufficient basis for clinical trials, and clinical validation is needed ( 45 ).…”
Section: Te Treatmentsmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previously described [33]. Briefly, CD31 (Abcam, UK), Ki67 (BD Biosciences, USA), E-CADHERIN (Santacruz, USA), CK14 (Abcam, UK), ER (GeneTex, USA), TOMM20 (Abcam, UK) and GFP (Santacruz, USA) was detected in fixed and paraffin embedded-endometrial tissue or organoids sections.…”
Section: Immunofluorescence and Microscopymentioning
confidence: 99%
“…Whole uteri were homogenized in Labozol (Cosmo, South Korea) and the complementary DNAs were synthesized as previously described [33]. RT-qPCR was performed on cDNA to assess the expression of genes of interest with SYBR Green (Enzynomics, South Korea).…”
Section: Quantitative Rt-pcr-based Analysis Of Mrna Expressionmentioning
confidence: 99%